2008
DOI: 10.1007/s12015-008-9008-2
|View full text |Cite
|
Sign up to set email alerts
|

Recent Progress on Tissue-Resident Adult Stem Cell Biology and Their Therapeutic Implications

Abstract: Recent progress in the field of the stem cell research has given new hopes to treat and even cure diverse degenerative disorders and incurable diseases in human. Particularly, the identification of a rare population of adult stem cells in the most tissues/organs in human has emerged as an attractive source of multipotent stem/progenitor cells for cell replacement-based therapies and tissue engineering in regenerative medicine. The tissue-resident adult stem/progenitor cells offer the possibility to stimulate t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
133
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 157 publications
(137 citation statements)
references
References 229 publications
(490 reference statements)
3
133
0
1
Order By: Relevance
“…Among them, the SHH protein is required for the regulation of multiple key cellular events in a wide range of adult tissue and organ types including bone marrow (BM), central nervous system and peripheral nerves, cardiovascular system, and epithelial tissues such as skin, lung, liver, gastrointestinal tract, pancreas, prostate, breast, and ovary (McMahon et al, 2003;Nielsen et al, 2004;Paladini et al, 2005;Katoh and Katoh, 2006;Sicklick et al, 2006;Vaillant and Monard, 2009). It has been shown that Hh proteins can promote the proliferation of diverse multipotent tissue-resident adult stem/progenitor cells, including hematopoietic, neural, skin, cochlear, gastrointestinal, hepatic, pancreatic, and mammary stem/progenitor cells, and thereby participate in cell replenishment and tissue regeneration and repair after severe injuries (Bhardwaj et al, 2001;Machold et al, 2003;McMahon et al, 2003;Nielsen et al, 2004;Ahn and Joyner, 2005;Paladini et al, 2005;Sicklick et al, 2005;Katoh and Katoh, 2006;Lau et al, 2006;Liu et al, 2006;Sicklick et al, 2006;Lin et al, 2007;Mimeault and Batra, 2008c). Hence, the SHH protein plays important roles in the replenishment of cells that are lost during tissue turnover and injuries.…”
Section: A Functions Of the Hedgehog Cascade In Adult Tissues And Thmentioning
confidence: 99%
“…Among them, the SHH protein is required for the regulation of multiple key cellular events in a wide range of adult tissue and organ types including bone marrow (BM), central nervous system and peripheral nerves, cardiovascular system, and epithelial tissues such as skin, lung, liver, gastrointestinal tract, pancreas, prostate, breast, and ovary (McMahon et al, 2003;Nielsen et al, 2004;Paladini et al, 2005;Katoh and Katoh, 2006;Sicklick et al, 2006;Vaillant and Monard, 2009). It has been shown that Hh proteins can promote the proliferation of diverse multipotent tissue-resident adult stem/progenitor cells, including hematopoietic, neural, skin, cochlear, gastrointestinal, hepatic, pancreatic, and mammary stem/progenitor cells, and thereby participate in cell replenishment and tissue regeneration and repair after severe injuries (Bhardwaj et al, 2001;Machold et al, 2003;McMahon et al, 2003;Nielsen et al, 2004;Ahn and Joyner, 2005;Paladini et al, 2005;Sicklick et al, 2005;Katoh and Katoh, 2006;Lau et al, 2006;Liu et al, 2006;Sicklick et al, 2006;Lin et al, 2007;Mimeault and Batra, 2008c). Hence, the SHH protein plays important roles in the replenishment of cells that are lost during tissue turnover and injuries.…”
Section: A Functions Of the Hedgehog Cascade In Adult Tissues And Thmentioning
confidence: 99%
“…Recently, it has been shown that MS cells can be found in almost any post-natal organs and tissues including adipose tissue (da Silva et al 2006;Mimeault and Batra 2008). This knowledge has enormous applications in veterinary medicine and tissue engineering for acute injuries and chronic disorders.…”
Section: Discussionmentioning
confidence: 99%
“…Among the tissues and organs harboring ASC, there are bone marrow, vascular walls, adipose tissues, skeletal muscles, heart, and brain, as well as epithelium of lung, liver, pancreas, digestive tract, skin, retina, breast, ovaries, prostate, and testis [81]. The bone marrow stem cell niche includes the hematopoietic stem cell population, which provides continuous renewal of blood cell lineages and the foundation of the immune system, and the mesenchymal stem cell population, responsible for osteogenic, adipogenic, and chondrogenic differentiation [82].…”
Section: Definition and Classificationmentioning
confidence: 99%